Pipe drafting and design - Parisher, Roy A.; Rhea, Robert A. (Boston : Gulf Professional Pub., 2002)
Pipe designers and drafters provide thousands of piping drawings used in the layout of industrial and other facilities. The layouts must comply with safety codes, government standards, client specifications, budget, and start-up date. Pipe Drafting and Design, Second Edition provides step-by-step instructions to walk pipe designers and drafters and students in Engineering Design Graphics and Engineering Technology through the creation of piping arrangement and isometric drawings using symbols for fittings, flanges, valves, and mechanical equipment. The book is appropriate primarily for pipe design in the petrochemical industry. More than 350 illustrations and photographs provide examples and visual instructions. A unique feature is the systematic arrangement of drawings that begins with the layout of the structural foundations of a facility and continues through to the development of a 3-D model. Advanced chapters discuss the customization of AutoCAD, AutoLISP and details on the use of third-party software to create 3-D models from which elevation, section and isometric drawings are extracted including bills of material. Covers drafting and design fundamentals to detailed advice on the development of piping drawings using manual and AutoCAD techniques 3-D model images provide an uncommon opportunity to visualize an entire piping facility Each chapter includes exercises and questions designed for review and practice.
Overview of pipe drafting and design -- Steel pipe -- Pipe fittings -- Flange basics -- Valves -- Mechanical equipment -- Flow diagrams and instrumentation -- Codes and specifications -- Equipment layout -- Piping arrangement drawings, sections, and elevations -- Standard piping details -- Piping systems -- Piping isometrics -- Customizing AutoCAD -- Three-dimensional modeling of piping systems.
Includes index.
Keywords: Piping -- Drawings -- Handbooks, manuals, etc; Piping -- Design and construction -- Handbooks, manuals, etc; Piping -- Drawing -- Handbooks, manuals, etc. Piping -- Design and construction -- Handbooks, manuals, etc; Electronic books